2016
DOI: 10.1371/journal.pone.0156317
|View full text |Cite|
|
Sign up to set email alerts
|

Study of Association between Pre-Senile Cataracts and the Polymorphisms rs2228000 in XPC and rs1042522 in p53 in Spanish Population

Abstract: PurposeTo determine if the presence of certain polymorphisms in the DNA repair gene XPC and the apoptosis inductor gene p53 is associated with pre-senile cataract development.MethodsWe have performed a retrospective study over three groups of patients. The group with pre-senile cataract formed by 72 patients younger than 55 with cataract surgery. The group with senile cataract formed by 101 patients older than 55 with cataract surgery. The group without cataract was formed by 42 subjects older than 55 without … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…There was a positive feedback between P53 and miR-34a (15)(16)(17). P53 is a transcription factor whose main function is to regulate the cell life cycle by controlling the expression of multiple genes, thus promoting apoptosis (18,19). Ji et al (20) found that P53 could regulate the cellular differentiation genes in the lens by regulating αA-and βA3/a1-crystallin genes.…”
Section: Discussionmentioning
confidence: 99%
“…There was a positive feedback between P53 and miR-34a (15)(16)(17). P53 is a transcription factor whose main function is to regulate the cell life cycle by controlling the expression of multiple genes, thus promoting apoptosis (18,19). Ji et al (20) found that P53 could regulate the cellular differentiation genes in the lens by regulating αA-and βA3/a1-crystallin genes.…”
Section: Discussionmentioning
confidence: 99%